1999
DOI: 10.1897/1551-5028(1999)018<0308:ptoftn>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Toxicity of Fluoranthene to Northern Leopard Frogs (Rana Pipiens)

Abstract: Rana pipiens larvae (96-118 h old) were exposed for 48 h in a flow-through system to clean water or five concentrations (0.89, 2.18, 6.99, 12.0, and 30.6 g/L) of the phototoxic polycyclic aromatic hydrocarbon (PAH) fluoranthene. Following this uptake period, the larvae were divided into four groups: one for immediate tissue residue analysis, a second for residue analysis following 48 h of depuration in clean water, and two for a 48-h exposure in clean water to ultraviolet (UV) light at two different levels. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…Tadpoles of northern leopard frogs (Rana pipiens) experienced similar results when they were exposed to 30.6 lg/L of fluoranthene and 250 lg/L of anthracene. When tadpoles were exposed to UV radiation, mortalities increased (Kagan et al 1984;Monson et al 1999). In our experiment, maximal aqueous concentrations of benzo(a)pyrene (17 lg/L), fluoranthene (13 lg/L) and anthracene (65 lg/L) were below these toxic concentrations.…”
Section: Survival and Growthmentioning
confidence: 48%
See 1 more Smart Citation
“…Tadpoles of northern leopard frogs (Rana pipiens) experienced similar results when they were exposed to 30.6 lg/L of fluoranthene and 250 lg/L of anthracene. When tadpoles were exposed to UV radiation, mortalities increased (Kagan et al 1984;Monson et al 1999). In our experiment, maximal aqueous concentrations of benzo(a)pyrene (17 lg/L), fluoranthene (13 lg/L) and anthracene (65 lg/L) were below these toxic concentrations.…”
Section: Survival and Growthmentioning
confidence: 48%
“…Amphibians can bioaccumulate PAHs (Grinfield et al 1986;Vojinovic-Miloradov et al 1996) but there is evidence that amphibians can develop an equilibrium in body concentrations after several days of exposure (Garrigues et al 2004). Oxidation and UV radiation can degrade parent PAHs and either make them less toxic or increase their toxicity by many times (Monson et al 1999, Albers 2003. For example, exposure of PAHs to ultraviolet (280-400 nm) radiation has increased toxicity by more than 100 times in bullfrogs (Rana catesbeiana) and the Spanish ribbed newt (Pleurodeles waltl) (Fernandez and l'Haridan 1992).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the photochemical effects of a compound depend on the dose (intensity · time) and not on intensity. This law has been supported by many reports (Ankley et al 1995;Monson et al 1999;Weinstein 2002), and is usually also assumed for complex photobiological reactions. It is possible that the intensity we employed in the pulsed UVB exposure may have exceeded the threshold level for the defense and recovery mechanisms in D. magna.…”
Section: -E Homo -E Lumo Gapmentioning
confidence: 53%
“…In that study, 62% of the accumulated pyrene was metabolized and/or eliminated in 12 hours. Monson et al [15] showed that Rana pipiens larvae eliminated 80% of accumulated fluoranthene after a 48-hour recovery period. These time frames are fairly rapid for PAHs with high molecular weights and lower water solubilities.…”
Section: Resultsmentioning
confidence: 99%